Perancangan Reponsive Layananan Sistem Informasi Perkuliahan Online Terhadap Mahasiswa Dan Dosen Pengampu Matakuliah - Sudarmaji Sudarmaji (Institut Informatika dan Bisnis Darmajaya, 2019)
The development of internet technology provides opportunities for applications in all types of human activities including special education for higher education in universities to improve the quality of education. This study discusses the importance of the elements that must be met when we build web-based academic applications with web technology as an information system service using an Android-based smartphone. As a sample in the research data, there were 168 or 50% of students involved in the total number of Computer Science students at the University of Muhammadiyah Metro Lampung, 336 people in the use of web-based lecture information system services. Improving the quality of lecture information system services is needed a response from students with the existence of this information system service by using questionnaires as responsive indicators of students. Online Information System Services lectures conducted by a lecturer at the Faculty of Computer Science, University of Muhammadiyah Metro. This research will also discuss open source as the foundation for disseminating lecture information system services that can be carried out by students and lecturers by using a variety of hardware one with a mobile system or smartphone.Keywords: Reponvive Services, Information Systems, Online Lectures